Trauma theory in Sándor Ferenczi's writings of 1931 and 1932 (2009)
The author states that it is Ferenczi?’s writings of 1931 and 1932 that exhibit the most conspicuous departures from Freud?’s ideas and at the same time contain Ferenczi?’s most original contributions. The texts concerned – Confusion of tongues between adults and the child (Ferenczi, 1932a), the Clinical Diary (Dupont, 1985), and some of the Notes and fragments (Ferenczi, 1930–32), all of which were published posthumously – present valuable and original theories on trauma which are significant not only in historical terms but also because the ideas concerned are relevant to our conception of clinical psychoanalysis today. The aim of this paper is to give an account of Ferenczi?’s trauma theory as it emerges from his writings of 1931–32 and to specify the points on which he differs from Freud.